2022
DOI: 10.1155/2022/2104056
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Individuals with Diabetes about Efficacy and Safety of Complementary and Alternative Medicines (CAM) in the Jazan Region, Saudi Arabia

Abstract: Background. CAM is widely accepted for the management of diabetes, and CAM users from many countries showed positive perception towards its use. However, little is known about the perception of individuals with diabetes in Saudi Arabia. Objectives. This study was aimed to assess the perception of the individuals with diabetes of Jazan region in Saudi Arabia towards CAM. Methods. An online, anonymous cross-sectional survey was designed and conducted between September 5 and December 31, 2021. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
3
2
Order By: Relevance
“…Furthermore, nearly half (45.3%) of our population used both CAM and DM medications. These results are similar to those reported in a study by Meraya et al ( 16 ), in which 34% of patients were using CAM along with modern medicine for DM control. Patients with chronic conditions such as diabetes are particularly likely to seek CAM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, nearly half (45.3%) of our population used both CAM and DM medications. These results are similar to those reported in a study by Meraya et al ( 16 ), in which 34% of patients were using CAM along with modern medicine for DM control. Patients with chronic conditions such as diabetes are particularly likely to seek CAM.…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaire comprised four major sections based on the literature ( 11 , 16 ). The first section gathered sociodemographic information on the participants, including age, gender, marital status, education status, employment status, and living area.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed variations in results regarding the use of CAM among type 2 diabetes patients. Our results were lower than the studies conducted in other parts of Saudi Arabia, such as in Riyadh at 84.6%, Jazan at 34%, and Jeddah at 64% [18][19][20]. Another study that was conducted in UAE reported that 39.3% of participants were CAM users since diagnosis [12].…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, most of the participants (76.7%) admitted that they counsel their doctor about using herbal products to control diabetes. These findings were higher than the results of two studies done in Saudi Arabia [ 18 , 19 ].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation